RACISM IN SELECTED SONGS OF THE ALBUM EVERYBODY BY LOGIC (2017) - Ariyj, - (Universitas Pendidikan Indonesia, 2023)
Racism has been a global issue for a very long time. Many people are trying to erase that stigma about certain races to create equality. There are many platforms and strategies people do to spread the messages of equality and spread awareness about racism. This study aims to explore and examine the concept of racism in songs related . Logic, the American rapper well known for his background as a biracial rapper, tries to spread awareness about racism based on his childhood experiences as a biracial kid in a racist society. In order to find the answer, this research uses qualitative methods by using lyrics as a primary source of data, and it uses DiAngelo's (2020) explanation about racism to explain what leads to parted experiences and acts of racism. This research found four types of racism experienced by Logic in the selected songs from his album 'Everybody' (2017): prejudice and stereotype, exclusion, racial violence, and identity invalidation. The purpose of this study is expected to raise a better awareness of the kinds of racism embedded in our daily lives.